152k views
4 votes
Solve the quadratic equation X^2+5x+6=0 using the completing the square method. Be sure to explain each step.

User JSager
by
4.9k points

1 Answer

0 votes

To complete the perfect trinomial, we add (5/2)² to the given equation and get:


x^2+5x+((5)/(2))^2+6=((5)/(2))^2.

Subtracting 6 we get:


x^2+5x+((5)/(2))^2=(25)/(4)-6=(1)/(4).

Therefore:


(x+(5)/(2))^2=(1)/(4).

Finally, we get:


\begin{gathered} x+(5)/(2)=\pm\sqrt{(1)/(4)}, \\ x=\pm(1)/(2)-(5)/(2). \end{gathered}

Answer:


\begin{gathered} x_=-3,\text{ or x=-2.} \\ \end{gathered}

User Sandwichnick
by
4.9k points